The Cost of Production of Capital - Bonar, J. (Quarterly Journal of Economics, 1889)
Journal Article The Cost of Production of Capital Get access J. Bonar J. Bonar Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 4, Issue 1, October 1889, Pages 81–83, https://doi.org/10.2307/1883003 Published: 01 October 1889